Concise Review: Considering Optimal Temperature for Short-Term Storage of Epithelial Cells - Khan, Ayyad Zartasht; Utheim, Tor Paaske; Jackson, Catherine Joan; Tønseth, Kim Alexander; Eidet, Jon Roger (Frontiers in Medicine, 2021)
Transplantation of novel, tissue-engineered products using cultured epithelial cells is gaining significant interest. While such treatments can readily be provided at centralized medical centers, delivery to patients at geographically remote locations requires the establishment of suitable storage protocols. One important parameter of storage technology is temperature. This paper reviews storage temperature for above-freezing point storage of human epithelial cells for regenerative medicine purposes. The literature search uncovered publications on epidermal cells, retinal pigment epithelial cells, conjunctival epithelial cells, corneal/limbal epithelial cells, oral keratinocytes, and seminiferous epithelial cells. The following general patterns were noted: (1) Several studies across different cell types inclined towards 4°C and 16°C being suitable short-term storage temperatures. Correspondingly, almost all studies investigating 37°C concluded that this storage temperature was sub-optimal. (2) Cell death typically escalates rapidly following seven to ten days of storage. (3) The importance of the type of storage medium and its composition was highlighted by some of the studies, however, the relative importance of storage medium vs storage temperature has not been investigated systematically. Although a direct comparison between the included investigations is not reasonable due to differences in cell types, storage media, and storage duration, this review provides an overview, summarizing the work carried out on each cell type during the past two decades.